2019
DOI: 10.1371/journal.pone.0211403
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization and time-stability of social hierarchies

Abstract: The formation and stability of social hierarchies is a question of general relevance. Here, we propose a simple generalized theoretical model for establishing social hierarchy via pair-wise interactions between individuals and investigate its stability. In each interaction or fight, the probability of “winning” depends solely on the relative societal status of the participants, and the winner has a gain of status whereas there is an equal loss to the loser. The interactions are characterized by two parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 114 publications
2
12
0
Order By: Relevance
“…Acronym [equation in (time scale) SI Appendix, section 10] Description Reactivity (initial) R 0 [6], MR 0 [11] Maximum instantaneous rate at which perturbations can be amplified.…”
Section: Namementioning
confidence: 99%
See 1 more Smart Citation
“…Acronym [equation in (time scale) SI Appendix, section 10] Description Reactivity (initial) R 0 [6], MR 0 [11] Maximum instantaneous rate at which perturbations can be amplified.…”
Section: Namementioning
confidence: 99%
“…S tability has been a core topic of research in complex systems across disciplines. From socioeconomic models of political regimes (1,2), to financial systems (3)(4)(5), social organizations (6,7), or biological systems of genetic regulatory circuits (8,9), the study of dynamical stability keeps drawing the attention of the scientific community. This interest has been particularly prominent in ecology, where it has fuelled decades of research (10)(11)(12)(13)(14)(15)).…”
mentioning
confidence: 99%
“…Empirical studies have indicated the presence of a "winner effect": An individual who participates in a favorable interaction, such as winning a fight or receiving an endorsement, increases their likelihood of being favored in future interactions (10,11). Both theoretical work (12)(13)(14)(15)(16)(17)(18)(19)(20) and controlled experiments in humans (21) suggest that winner effects are sufficient (though not necessary) to form stable hierarchies. Mechanistic explanations of winner effects vary.…”
mentioning
confidence: 99%
“…Empirical studies have indicated the presence of a winner effect: an individual who participates in a favorable interaction, such as winning a fight or receiving an endorsement, increases their likelihood of being favored in future interactions [Chase et al, 1994;Hogeweg and Hesper, 1983]. Both theoretical work [Bonabeau et al, 1995[Bonabeau et al, , 1996Hemelrijk, 1999;Ben-Naim and Redner, 2005;Miyaguchi et al, 2020;Pósfai and D'Souza, 2018;Hickey and Davidsen, 2019;Vehrencamp, 1983;Sánchez-Tójar et al, 2018] and controlled experiments in humans [Salganik et al, 2006] suggest that winner effects are sufficient (though not necessary) to form stable hierarchies. Mechanistic explanations of winner effects vary.…”
mentioning
confidence: 99%